2008
DOI: 10.1128/iai.00069-08
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis of UropathogenicEscherichia coliEvasion of the Innate Immune Response in the Bladder

Abstract: In the urinary tract, the innate immune system detects conserved bacterial components and responds to infection by activating the proinflammatory transcription factor NF-B, resulting in cytokine secretion and neutrophil recruitment. Uropathogenic Escherichia coli (UPEC), however, has been shown to evade the host innate immune response by suppressing NF-B activation in urothelial cells, which results in decreased cytokine secretion and increased urothelial apoptosis. To understand the molecular basis of UPEC mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 52 publications
1
74
1
1
Order By: Relevance
“…We did not observe suppression of cytokine expression and/or neutrophil recruitment by our UPEC strains, regardless of HlyA1 production, by 6 h (data not shown) or 24 h after inoculation, as has previously been reported by others (46,(54)(55)(56)(57)(58). These groups measured the cytokine IL-6 and/or IL-8 after infection of different strains of bladder epithelial cell lines with clinical isolates (NU14, F11, UTI89) or with laboratory strains (HB101, MG1655) and showed that the laboratory strains induced significantly more cytokine release than the clinical isolates (54)(55)(56)(57).…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…We did not observe suppression of cytokine expression and/or neutrophil recruitment by our UPEC strains, regardless of HlyA1 production, by 6 h (data not shown) or 24 h after inoculation, as has previously been reported by others (46,(54)(55)(56)(57)(58). These groups measured the cytokine IL-6 and/or IL-8 after infection of different strains of bladder epithelial cell lines with clinical isolates (NU14, F11, UTI89) or with laboratory strains (HB101, MG1655) and showed that the laboratory strains induced significantly more cytokine release than the clinical isolates (54)(55)(56)(57).…”
Section: Resultssupporting
confidence: 67%
“…Lipid A, a TLR4 ligand that is well-known to elicit a very strong innate immune response, is more accessible on rough strains than it is on smooth strains. Billips et al and Hunstad et al demonstrated that UPEC strains that contain mutations in genes involved in LPS biosynthesis, particularly O-and core-polysaccharide antigen synthesis, induced more IL-6 and IL-8 from urothelial cells in vitro than the isogenic smooth parent strains (46,57). Thus, though they and others found that the type of LPS expressed by the challenge strain (rough versus smooth) was not the only factor that contributed to immune suppression, rough LPS expressed by the more immune-stimulatory laboratory strains clearly played a role.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies reported suppression of cytokine production in response to UPEC in vitro infection. 35,64,65 This discrepancy with our results is likely due to differences in post-infection incubation time and is therefore reflecting differences between acute and persistent phase of infection.…”
Section: Discussioncontrasting
confidence: 57%
“…Lymphocytes were isolated by homogenizing spleens of B6 or TNF-␣ Ϫ/Ϫ mice. Erythrocytes were eliminated by incubation of the homogenates in lysis buffer (160 mM NH 4 Cl, 170 mM Tris; pH 7.4). Splenic naïve CD4 ϩ T cells were purified with a MACS negative selection kit (Miltenyi, Bergisch Gladbach, Germany) by following the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%